Social Mobility In Danny Boyle's And Loveleen's Slumdog Millionare: Marxist Approach - Eraditya S, Picend; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S, M.Hum (2015)
This study is about experience of life is way to change the destiny. The problem of this study is how social mobility in Danny Boyle's and Loveleen's Slumdog. The object of the study is Slumdog Millionare movie by Danny Boyle and Loveleen. It used marxist approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is Slumdog Millionare movie and the secondary data source is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusion. Based on the analysis it is clear that there is a close relation between structural analysis of this film and marxist analysis of Slumdog Millionare movie. Danny Boyle and Loveleen wants to show how experience of life can change the destiny through Slumdog Millionare movie.